Three different Plasmodium species show similar patterns of clinical tolerance of malaria infection - Muller, I.; Genton, B.; Rare, L.; Kiniboro, B.; Kastens, W.; Zimmerman, P.; Kazura, J.; Alpers, Michael Philip; Smith, T. (BioMed Central Ltd, 2009)
Abstract: Background: In areas where malaria endemicity is high, many people harbour blood stageparasites without acute febrile illness, complicating the estimation of disease burden from infectiondata. For Plasmodium falciparum the density of parasitaemia that can be tolerated is low in theyoungest children, but reaches a maximum in the age groups at highest risk of infection. There islittle data on the age dependence of tolerance in other species of human malaria.Methods: Parasite densities measured in 24,386 presumptive malaria cases at two local healthcentres in the Wosera area of Papua New Guinea were compared with the distributions of parasitedensities recorded in community surveys in the same area. We then analyse the proportions ofcases attributable to each of Plasmodium falciparum, P. vivax, and P. malariae as functions of parasite density and age using a latent class model. These attributable fractions are then used to compute the incidence of attributable disease.Results: Overall 33.3%, 6.1%, and 0.1% of the presumptive cases were attributable to P. falciparum,P. vivax, and P. malariae respectively. The incidence of attributable disease and parasite densitybroadly follow similar age patterns. The logarithm of the incidence of acute illness is approximatelyproportion to the logarithm of the parasite density for all three malaria species, with little agevariation in the relationship for P. vivax or P. malariae. P. falciparum shows more age variation indisease incidence at given levels of parasitaemia than the other species.Conclusion: The similarities between Plasmodium species in the relationships between parasitedensity and risk of attributable disease are compatible with the hypothesis that pan-specificmechanisms may regulate tolerance to different human Plasmodia. A straightforward mathematicalexpression might be used to project disease burden from parasite density distributions assessed in community-based parasitological surveys.